Generation Z’s Views on the Ethical Use of Artificial Intelligence Tools in Accomplishing Academic Outputs - LLANES, NELJHON PHILIP; Talamor, Miles Aishley; Jaspe, Shiena Marie; Pedroso, John Erwin (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
The advent of technology has served as the fount of the emerging Artificial Intelligence tools, now often used in the field of academe benefiting students with the ease to accomplish academic tasks. While several people are confused about the different risks and benefits of using AI tools, this study highlights how students who are categorized as Generation Z view the ethical use of AI tools in accomplishing their academic outputs. A qualitative research design is used with the participation of the ten (10) AI-experienced students from WVSU - Integrated Laboratory School via purposive sampling. Despite AI’s ambivalence, results revealed that they view AI tools as a helpful tool for academic success which has a corresponding responsibility, discipline and orientation. This opens up the necessity for the institutions to provide and strengthen clear ethical guidelines, policies and digital literacy programs to preserve academic integrity as AI tools advance nowadays.